Multi-protomics analysis identified host cellular pathways perturbed by tick-borne encephalitis virus infection - Liyan Sui; Wenfang Wang; Xuerui Guo; Yinghua Zhao; Tian Tian; Jinlong Zhang; Heming Wang; Yueshan Xu; Hongmiao Chi; Hanxi Xie; Wenbo Xu; Nan Liu; et al. (Nature Communications)
Abstract Tick-borne encephalitis virus (TBEV) represents a pivotal tick-transmitted flavivirus responsible for severe neurological consequences in Europe and Asia. The emergence of TBEV genetic mutations and vaccine-breakthrough infections, along with the absence of effective vaccines and specific drugs for other tick-borne flaviviruses associated with severe encephalitis or hemorrhagic fever, underscores the urgent need for progress in understanding the pathogenesis and intervention strategies for TBEV and related flaviviruses. Here we elucidate cellular alterations in the proteome, phosphoproteome, and acetylproteome upon TBEV infection. Our findings reveal a substantial impact of TBEV infection on the innate immune response, ribosomal biogenesis, autophagy, and DNA damage response (DDR). Mechanically, the non-structural protein NS5 of TBEV impedes DNA damage repair by interacting with SIRT1 to suppress the deacetylation of KAP1 and Ku70. Additionally, the precursor membrane protein prM induces autophagy via associating with AKT1 while constrains autolysosome formation through binding to VPS11. Inhibitors targeting DDR, as well as specific kinases, exhibit potent antiviral activity, suggesting the dysregulated pathways and kinases as potential targets for antiviral intervention. These results from our study contribute to elucidating the pathogenesis and offers insights for developing effective antiviral drugs against TBEV and other tick-borne flaviviruses.